EMPLOYMENT AND INCOME GENERATION THROUGH LIVESTOCK AMONG WOMEN SELF HELP GROUPS – A STUDY IN THIRUVANNAMALAI DISTRICT., TAMIL NADU* - B. Jaya Varathan; M. Prabu; A. Serma Saravana Pandian; G. Senthilkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was undertaken in Thiruvannamalai district of Tamil Nadu to analyze the socio-economic characteristics, income and employment pattern of Self Help Group members and non-members through livestock rearing. Data pertaining to the objectives of the study were collected from 120 sample respondents using pre-tested interview schedule. The results showed that, out of 60 SHG women livestock farmers, the presence of landless category was the highest (76.67 per cent) and out of 60 women livestock farmers from non-members of SHG, the marginal farmer category were the highest (50.00 %). It was observed that 77 per cent of the SHG respondents were from landless category. The overall average land holding size of SHG member and non-member was 0.67 and 1.43 acres respectively which showed that economically weaker sections of the women farmers were participating more in the SHG programme. The average livestock holding size of SHG members were low (1.94) compared to non-members (2.37). SHG members having secondary level of education were at a higher level (58.33 %) than non-members (9 %). The analysis on income and employment pattern of sample respondents clearly indicated that the livestock farming engaged more man-days (121) and fetched higher annual income (Rs.28874) among SHG members compared to non-members (51 man-days and Rs.24687). The study distinctly indicated the favorable impact of the SHG programme on the socio-economic characteristics, income and employment dimensions among SHG women members.